1990
DOI: 10.1111/j.1474-919x.1990.tb01010.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental feeding in the Red‐throated Diver Gavia stellata

Abstract: We describe parental feeding by Red‐throated Divers Gavia stellata from 14.2–44.7 h of observation on each of eight pairs, coordinated with simultaneous observations at potential fishing lakes, in southwest Sweden. All pairs bred on small tarns (0.8–10 ha), normally devoid offish, and foraged in larger freshwater lakes 1.9–7.7 km away from the breeding site. Most pairs directed the majority of the foraging trips to the same lake. On average, parents made seven foraging trips per day per young. Both parents con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Finland Iceland freshwater (Eriksson et al 1990, Eriksson and Sundberg 1991, Duckworth et al 2020b) and marine environments during the breeding season (Reimchen and Douglas 1984, Black et al 2015, Rizzolo et al 2015. As predicted, all diving metrics (dive depth and dive duration) differed between Finland and at least one of the other two sites (Table 1).…”
Section: Scotlandmentioning
confidence: 64%
See 3 more Smart Citations
“…Finland Iceland freshwater (Eriksson et al 1990, Eriksson and Sundberg 1991, Duckworth et al 2020b) and marine environments during the breeding season (Reimchen and Douglas 1984, Black et al 2015, Rizzolo et al 2015. As predicted, all diving metrics (dive depth and dive duration) differed between Finland and at least one of the other two sites (Table 1).…”
Section: Scotlandmentioning
confidence: 64%
“…Instead it appears that the tracked divers may have adapted their foraging strategy via prey selection, rather than increasing the number of foraging trips or foraging intensity through time. This is suggested by earlier observations of RTDs from Sweden, where it was found that the number of foraging trips did not change as the breeding season progressed, but instead the size of the prey brought back by the parents changed (Eriksson et al 1990). This effect was particularly noticeable when the chicks were very young (Reimchen and Douglas 1984).…”
Section: Scotlandmentioning
confidence: 68%
See 2 more Smart Citations
“…In contrast, the Red-throated Diver Gavia stellata breeds at small lakes and tarns (mostly <1ha) often devoid of fish, and the non-fledged chicks are fed with fish caught by the parents in neighbouring larger lakes or at sea up to a distance of almost 10 km. Furthermore, the Red-throated Divers are more restrictive in their choice of fishing lakes than the Black-throated Divers; the chicks are primarily fed with cyprinid and salmonid fish, and abundance of prey fish is as important as distance to alternative foraging lakes (Eriksson et al 1990, Eriksson & Sundberg 1991, Eriksson & Johansson 1997. For pairs breeding in coastal areas, e.g.…”
Section: Discussionmentioning
confidence: 99%